Modifications in the Revised National Tuberculosis Control Program to achieve universal access to tuberculosis care - Saurabh Ram Bihari Lal Shrivastava; Prateek Saurabh Shrivastava; Jegadeesh Ramasamy (Wolters Kluwer Medknow Publications, 2014)
Global Tuberculosis Report - 2012, released by the World Health Organization (WHO) has revealed that in the year 2011 alone, 11.7 million new cases of tuberculosis (TB) have been reported worldwide, of which India contributed to almost one-quarter of the cases. Considering the global distribution, magnitude of the problem, serious impact on the quality of life, and high mortality rates; TB in today's world is the biggest public health disease of an infectious nature. Revised National Tuberculosis Control Program (RNTCP) has been geographically scaled-up and updated on multiple fronts based on the epidemiology of disease, infield practical experience, WHO's recommendations, and the successful implementation of different strategies in high burden countries. Refinement in the program has been observed in different fields such as diagnostics, treatment, involvement of medical college and private sector, along with some innovative measures. To conclude, strengthening of the RNTCP program has been planned in a comprehensive manner and due attention has been given to encourage and actively involve all the stakeholders so that global vision to achieve universal access to TB care can be accomplished.